Operative shoulder instability injury management in Australian Football League players: A case series. Issue 8 (August 2018) - Bonacci, Jason; Manson, Brent; Bowe, Steven J.; Gill, Stephen; Seward, Hugh; Hoy, Greg; Page, Richard
Abstract: Objectives: The purpose of this study was to review the surgical management procedures of shoulder instability injuries in Australian Football League (AFL) players, and determine outcomes regarding return to sport and injury recurrence. Design: Retrospective cohort study. Methods: Elite AFL players with shoulder instability resulting in surgery were assessed in a retrospective cohort design (72 players/77 shoulders). Type of initial injury, surgical management, return to sport and injury recurrence were obtained. The mean follow-up period post-surgery was 2.9 years. Return to sport outcomes were compared between arthroscopic and open surgery using a Kaplan–Meier survival analysis. Logistic regression modelling was used to determine associations between injury recurrence, type of injury, participant age and method of surgery. Results: Shoulder instability injuries occurred most frequently during tackling (40%). Arthroscopic surgery was preferred for primary shoulder instability. Nine (16%) recurrences occurred in those who underwent arthroscopic surgery compared to two (9%) following open surgery. Return to the elite level was slightly but significantly (2 weeks, p = 0.049) longer for open compared to arthroscopic surgery. Recurrence was 5 times more likely if the primary injury was a dislocation and more likely in players who were younger at the time of surgery. Conclusion: Tackling was the predominant mechanism for shoulder instability injuries in AFL players and arthroscopic surgery was more commonly performed for primary injuries. Sustaining a dislocation as the primary injury and younger age increased the likelihood of recurrent instability. Careful consideration should be given to the operative management of these individuals.